Synthesis of Seleno Oxindoles via Electrochemical Cyclization of N‐arylacrylamides with Diorganyl Diselenides. Issue 1 (18th November 2020) - Wang, Xin‐Yu; Zhong, Yuan‐Fang; Mo, Zu‐Yu; Wu, Shi‐Hong; Xu, Yan‐Li; Tang, Hai‐Tao; Pan, Ying‐Ming
Abstract: The tandem cyclization of acrylamide with diselenides facilitated by electrochemical oxidation was successfully developed. This strategy provided an environmentally friendly method for the construction of C−Se bond. A series of seleno oxindoles with pharmacological activity were obtained by using this well‐designed tandem cyclization strategy. The in vitro antitumor activity of the compounds was also screened through MTT assay. Results showed that the seleno oxindoles exhibited better antitumor activity than other oxindole derivatives. Abstract :